To kill a mockingbird - Lee, Harper (New York : Perennial, 2002)
Scout Finch, the young daughter of a local attorney in the Deep South during the 1930s, tells of her father's defense of an African-American man charged with the rape of a white girl.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: African Americans -- Fiction; Fathers and daughters -- Fiction; Girls -- Fiction; Race relations -- Fiction; Trials (Rape) -- Southern States -- Fiction; African Americans -- Fiction; Bildungsromans; Domestic fiction; Father-daughter relationship -- Fiction; Girls -- Fiction; Legal stories; Race relations -- Fiction; Trials (Rape) -- Fiction; Southern States -- Fiction; Southern States -- Fiction; Bildungsromans; Domestic fiction; Legal stories